A study on the soil resistance distribution predicted by CAPWAP analysis - Goh, Chai Heng. (2009)
This dissertation deals with the pile driving analysis of precast concrete piles used to support container stacking yard structure.The main purpose of this dissertation is to improve confidence in the results obtained from curve matching program namely CAPWAP through a better understanding of the influence of soil damping parameters on soil resistance estimation.